Labor income inequalities and tourism development in Argentina: A regional approach. Issue 8 (December 2019) - Porto, Natalia; Espinola, Natalia
This study aims to explore the regional wages inequalities and its relationship with the development of tourism and amenities endowment. We estimate a spatial error model for 29 metropolitan agglomerations in Argentina during the period 2004–2015. Four indices of touristic amenities that interact with tourism employment—as a proxy for tourism development—in labor income inequality estimations are used. Results show that the labor income distribution depends on the natural resources endowment, as well as the development of tourism in the agglomerates. A more equal distribution of labor income is observed in the agglomerates that have a greater presence of water-based resources, while the relationship is inverse in agglomerates with a greater presence of land-based resources. Also, the tourism employment has an unequal effect on labor income. In conclusion, the study shows the relevance of including aspects of regional development and resource endowment in the analysis of income inequality.